TIME-DRIVEN ACTIVITY-BASED COSTING DALAM PENETAPAN HAR-GA POKOK SEWA KAMAR DAN PROFITABILITAS PELANGGAN PADA HOTEL BINTANG 2 DAN 3 - Linggardjaja, Irene Kristanti; Handoko, Jesica; Oki, Ariston (Widya Mandala Surabaya Catholic University, 2012)
Hospitality businesses are growing so fast today, therefore a company needs accurate cost information for management’s deci-sion making. The traditional and ABC method’s shortcoming had led expertise to develop a better cost calculation method, Time-Driven Activity-Based Costing (TDABC). These qualitative research objectives were to try out and compare TDABC method im-plementation to calculate product cost and customer’s profitability in 2 stars and 3 stars hotel. The research objects are 88 Hotel Embong Malang Surabaya as 2 stars hotel and Grand Hotel Surabaya as 3 stars hotel. The research design is exploratory research with no hypothesis. This research used financial data and another qualitative data which are obtained directly through documenta-tion, interview, and direct observation in research objects. The data was analyzed by calculate product cost and customer’s profita-bility with traditional method and TDABC method. The research results showed that TDABC method is more suitable for 3 stars hotel than 2 stars hotel in calculating product cost because of high diversity product in 3 stars hotel. The results also showed that TDABC method doesn’t give a big impact in calculating customer’s profitability due to low diversity customers in both research objects.